Globalisation, localisation and protected areas - Sayer, Jeffrey A. (1999)
Processes of economic integration and growing economic influence of corporations are leading to greater efforts among people in all countries to protect the lifestyles and habitats that they value. For conservation organizations, the first challenge is clearly defining objectives and priorities on what to conserve, followed by mobilising the best available science and emerging techniques of working with local human communities to determine the most effiecient way of achieving the agreed conservation goals at the least social cost. Greater transparency, obejectivity and fairness must be essential elements in the process of allocating land for various purposes. For conservationists, the critical task is to determine the optimal extent, location and management of areas needed to achieve an acceptable balance between the development needs of local people and global biodiversity conservation needs. The inevitable trade-offs between biodiversity conservation and other uses of natural areas are more likely to be widely accepted if they are made in transparent manner with the full participation of all people concerned, with related economic costs and benefits allocated in an equitable manner. IUCN needs to play a leadership role in helping people protect their land against global pressures and enable the to be fairly compensated for any costs they may incur when they live in areas whose biodiversity values are primarily global and not local